Possibility of Neoplastic Transformation of Ovarian Endometriosis - A. Levakov , Sergey; A. Gromova, Tatyana (International Journal of Psychosocial Rehabilitation, 2020)
The aim of the study was to investigate the features of neoplastic endothelial transformation in the foci of ovarian endometriosis (OE). Materials and Methods: Histologic and immunohistochemical methods were used for the study of 78 and 35 cases of OE, respectively, and 8 cases of adenocarcinomas. The authors used antibodies to Ki-67, Всl-2, р53, and nuclear hepatocytes factor 1 beta (HNF-1β). Results: Epithelial walls of endometrial cysts had syncytial papillary changes (39.7%), metaplasia with hobnaillike cells (15.4%), atypia of epithelium with fluctuation of the expression of Ki-67 and Всl-2 from low to relatively high (41.0%), and the expression of р53 that tended to increase. The expression of HNF-1β in lesions without atypia was revealed in 56.3% of cases, and in lesions with atypia—in 94.7%, and was identified only in clear cell adenocarcinomas. Conclusion: Hyperexpression of HNF-1β suggested adaptive character and histogenetic association of OE with clear cell ovarian tumors.